MENUJU DAMPAK SOSIAL YANG BERKELANJUTAN: MEMBANGUN KESEJAHTERAAN SOSIAL DI CU LESTARI WONOSOBO: TOWARDS SUSTAINABLE SOCIAL IMPACT: BUILDING SOCIAL WELFARE IN CU LESTARI WONOSOBO - Stephanus Eri Kusuma; Januari Ayu Fridayani (MESTAKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
This community service program aims to build social welfare in Cu Lestari, Wonosobo. Through a participatory approach, the local community actively engages in formulating sustainable solutions to improve social conditions in the area. The focus of the program includes aspects such as education, health, and economics, with the goal of strengthening the foundation of welfare. The importance of this program lies in the urgent need to understand and address the social challenges faced by the community in Cu Lestari. With a collaborative approach, the program aims to provide sustainable positive impact, enhance the quality of life, and create positive changes in the daily lives of the residents. The community service method involves a series of participatory activities, ranging from problem identification to the planning and implementation of solutions together. The results include improved access to education, better healthcare services, and broader economic opportunities for the Cu Lestari community.